Testing ivermectin-based solid dispersion preparations obtained by different techniques against parasitic diseases of domestic animals - M. B. Musaev; I. Kh. Shakhbiev; A. Z. Jamalova (Российский паразитологический журнал)
The purpose of the research is to develop the production of ivermectin-based complex solid dispersion preparations with water-soluble polymer fillers using the technique previously developed in the VNIIP – FSC VIEV with a solvent, as well as the INEOS RAS (Nesmeyanov Institute of Organoelement Compounds RAS) technique in one stage without involving liquid phases, and their comparative performance testing against parasitosis of animals.Materials and methods. Preparation 1 was developed using the technique developed in the VNIIP – FSC VIEV in several stages, and preparation 2 was developed using the INEOS RAS technique in one stage. A comparative performance test of the above preparations was conducted on three private Chechen Republic farms on 870 Tushino sheep and 57 local goats spontaneously infected with gastrointestinal Strongylata. In the first experiment, the sheep (n = 130) were divided into 4 groups of 30–35 animals each on the analog principle. The sheep from the first and second experimental groups were given preparations 1 and 2 orally in the suspension formulation at doses of 0.2 mg/kg by active substance. The third and fourth groups of 35 sheep each were treated with the same preparations mixed with combined feed at the same dose, by the group method only. In the second experiment, 140 sheep and 57 goats were treated once, individually, with preparation 1 at a dose of 0.2 mg/kg in the suspension formulation. The third experiment on testing preparation 1 was conducted on 600 sheep, 217 bull calves, 165 horses, and 15 dogs in production conditions.Results and discussion. The solubility of preparation 1 increased by 7.1, and preparation 2 by 4.7. A HPLC analysis confirmed 95.0% preservation of ivermectin in both preparations. One hundred percent efficacy against gastrointestinal nematodes in sheep was confirmed for preparations 1 and 2 obtained by different techniques, given individually, once, at a dose of 0.2 mg/kg in the suspension formulation. The treating of the sheep with preparation 1 mixed with combined feed by group feeding obtained 100% efficacy, and 94.6% for preparation 2. The deworming of the sheep in the second experiment showed 100% efficiency for preparation 1 given individually, once, at a dose of 0.2 mg/kg by active substance in the suspension formulation. The testing of complex preparation 1 at a dose of 0.2 mg/kg in the third experiment obtained 100% efficacy against gastrointestinal nematodes in horses, young cattle, sheep, goats, and dogs. No side effects were observed in the animals after deworming.